ANALISIS KETERSEDIAAN DAN KONDISI MEDIA PEMBELAJARAN IPA PADA KELAS TINGGI SEKOLAH DASAR DI KECAMATAN CILEUNYI, KABUPATEN BANDUNG - Roni Wahyu Wandani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to examine the state and accessibility of science education materials in upper-grade elementary school classrooms in Bandung Regency's Cileunyi District. 35 upper-grade teachers from 24 elementary schools—18 public and 6 private—participated in the study, which used a quantitative descriptive methodology. A 4-point Likert scale questionnaire was used to collect data between May and July of 2026. Aspects of science learning media availability and condition, including media completeness, maintenance, storage facilities, and staff in charge of media checks, were taken into consideration when developing the study instrument. Descriptive statistics were used to assess the data by computing score achievement percentages and categorizing the results. The findings show that, with an achievement level of 61.67%, the availability of science learning materials falls into the "complete" category. In the meantime, the media's success level of 59.71% places it in the "adequate" category. In terms of condition, storage facilities scored 65.36% (good), inspection staff scored 56.43% (adequate), and media maintenance scored 55.00% (sufficient). These results show that science education materials are reasonably accessible in primary schools; however, their state and administration need to be improved, especially with regard to upkeep and routine inspections. This study offers an empirical summary of the availability and state of science learning materials, providing schools with a foundation for improving learning resource management and guaranteeing that media continue to be operational, well-maintained, and prepared for use in supplementing science instruction in upper-grade elementary classes.